A comparative evaluation of intraperitoneal instillation and periportal infiltration of 0.375% ropivacaine with dexmedetomidine and nalbuphine as adjuvants for post-operative analgesia in laparoscopic cholecystectomy - Shagufta Bhat,; Tufail Ahmad Sheikh,; Rajesh Angral,; Heena Saini,; Anshuman Mahesh Chander, (Asian Journal of Medical Sciences, 2023)
Background: Intraperitoneal instillation (IPI) of local anesthetic agents into peritoneal cavity has proved to be an effective method of post-operative analgesia in laparoscopic cholecystectomy (LC). The addition of adjuvants such as narcotics or α2-agonists has been proposed to prolong the duration of post-operative analgesia. Aims and Objectives: This study aimed to compare post-operative analgesia of IPI and periportal infiltration of ropivacaine plus dexmedetomidine with ropivacaine plus nalbuphine in patients undergoing LC. Materials and Methods: This was a comparative, prospective, randomized controlled double-blind study conducted on total of 100 patients (American Society of Anesthesiologists class I and II) planned for LC who were randomly divided into two groups of 50 patients: Group Ropivacaine+Dexmedetomidine (RD) received IPI and periportal infiltration of 150 mg of ropivacaine (0.375%) and dexmedetomidine (1 μg/kg) diluted with normal saline to 40 mL and Group Ropivacaine+Nalbuphine (RN) received 150 mg of ropivacaine (0.375%) and 10 mg nalbuphine diluted with normal saline to 40 mL. Post-operative pain was assessed by Visual Analogue Score, time to first request of analgesia, and total amount of rescue analgesics given in 24 h and side effects were noted. Data were analyzed by Student’s independent t-test and Chi-square test using SPSS version 20.0. Results: Overall Visual Analog Scale scores (1.38±0.78 vs. 2.59±1.15), time to first request of analgesia (7.3±3.74 vs. 4.2±2.71), and total analgesic consumption (82.4±15.34 vs. 158.5±16.19) were significantly lower in the RD group compared to the RN group. Among post-operative adverse events, the incidence of post-operative nausea and vomiting was significantly higher in the RN group. Conclusion: The addition of dexmedetomidine appears to be superior to nalbuphine in terms of prolonged post-operative analgesia, lesser requirement of rescue analgesia, and less complications.